Air preheating systems for low-temperature drying - Aldas, Rizaldo E. (1997)
Low temperature drying is a slow drying process but an economical and energy efficient method resulting to high quality grain as it utilizes ambient air or lightly preheated air. Its operation requires knowledge of the ambient condition to know when to operate the air preheating system. It also requires an appropriate air preheating system which can endure long hour of operation and with controllable temperature to protect the grain. Thus some heating systems which may tapped for low temperature drying were evaluated. Drying tests were conducted to assess the performance of the pot-type kerosene burner resulted to fuel consumption of 0.68 to 0.90 li/hr and drying air efficiency of 36 to 50%. It also resulted to milled grain quality which is comparable with sundried and shade dried samples, however, controlling the temperature was still difficult and it produced high amount of combustion product that went into the bulk of the grain. On the other hand, the potentials of utilizing waste heat from an internal combustion engine were explored by using a 6 hp gasoline engine to run a blower in the test duct that simulated the dyer's plenum. The potential waste heat energy was directly proportional with the fuel consumption and engine brake horsepower while the fuel consumption was directly related with the airflow rate and static pressure. A temperature difference of around 6.4 K was possible with bare engine and around 8.6 K for an engine with housing. Meanwhile, a compact, lightweight and low-cost semi-automatic rice hull furnace for low temperature drying was designed and evaluated. The furnace which weigh around 35 kg used a piston type mechanism to provide feeding rate of around 3 to 7 kg/hr. It has a burning efficiency of 90 to 95% and drying air efficiency of 40 to 80%. The ash was discharged through the cyclonic compartment and air-sweep floor. Conducted drying tests resulted to excellent milled grain quality, an almost theoretical moisture reduction process, and clean dried grain which indicated that the furnace was effective in separating the ashes from the heated air.
Computer print-out.
Thesis (M.S. Energy Engineering)--University of the Philippines Diliman.
Keywords: Drying; Grain -- Drying. -- Philippines; Rice hulls as fuel -- Philippines; Rice -- Drying. -- Philippines